Toward ESG Alpha: Analyzing ESG Exposures through a Factor Lens. Issue 1 (2nd January 2021) - Madhavan, Ananth; Sobczyk, Aleksander; Ang, Andrew
Abstract : Using data on 1, 312 active US equity mutual funds with 3.9 trillion in assets under management, we analyzed the link between funds' bottom-up, holdings-based environmental, social, and governance (ESG) scores and funds' active returns, style factor loadings, and alphas. We found that funds with high ESG scores have profiles of factor loadings that are different from those of low-scoring ESG funds. In particular, funds with high environmental scores tend to have high quality and momentum factor loadings. In partitioning the ESG scores into components that are related to factors and idiosyncratic components, we found strong positive relationships between fund alphas and factor ESG scores. Abstract : Disclosure: The authors report no conflicts of interest. The views expressed here are ours alone. This material is not intended to be relied upon as a forecast, research, or investment advice and is not a recommendation, offer, or solicitation to buy or sell any securities or to adopt any investment strategy. The authors have not received any outside funding for this research. Editor's Note Submitted 1 June 2020 Accepted 18 August 2020 by Stephen J. Brown This article was externally reviewed using our double-blind peer-review process. When the article was accepted for publication, the authors thanked the reviewers in their acknowledgments. Keith H. Black, CFA, and one anonymous reviewer were the reviewers for this article.